PENGARUH LOCUS OF CONTROL, PERCEIVED RISK, VOTER DECISION INVOLVEMENT dan VOTER SATISFACTION TERHADAP VOTING STABILITY PEMILIH - Ayu Ekasari (Universitas Trisakti, 2006)
The study examines the electoral psychology of Indonesian voters during the presidential Election 2004 by applying consumer behavior theory. The focus of the research is to explore the effects of locus of control, perceived risk, voter decision involvement and voter satisfaction on voling stability. The results indicated that tocus of control influences perceived risk, then, perceived risk influences voter decision involvement. Nexl, voter decision involvementinfluences voter satisfaction, which in tun influences voting slability. This means that the propensity to vote for the same candidate in the next election is influenced by voters' psychological characteristics.